Profiling of the antibody response to attenuated LC16m8 smallpox vaccine using protein array analysis - Eto, Akiko; Fujita, Masanori; Nishiyama, Yasumasa; Saito, Tomoya; Molina, Douglas M.; Morikawa, Shigeru; Saijo, Masayuki; Shinmura, Yasuhiko; Kanatani, Yasuhiro (Vaccine, 2019)
Concerns about bioterrorism and outbreaks of zoonotic orthopoxvirus require safe and efficacious smallpox vaccines. We previously reported the clinical efficacy and safety profiles of LC16m8, a live, attenuated, cell culture-derived, smallpox vaccine, examined in over 3000 healthy Japanese adults with various vaccination histories. In this study, serum of approximately 200 subjects pre and post LC16m8 vaccination were subjected to a vaccinia virus-specific protein array to evaluate the proteome-wide immunogenicity. The relationships between antigen-specific antibodies and plaque reduction neutralization titers were analyzed. LC16m8 induced antibodies to multiple vaccinia antigens in primary-vaccinated individuals and yielded effective booster responses in previously vaccinated individuals, demonstrating similar antibody profiles to those reported for other vaccinia virus strains. Several immunodominant antigens were indicated to be important for neutralization of the intracellular mature virion. The similarity of antibody profiles between LC16m8 and other smallpox vaccine strains supports the immunogenicity and protective efficacy of LC16m8.